What does it take to scale an agricultural innovation? Loraine Ronchi talks with Agnes Kalibata - Wong, Madeline (CGIAR, 2024)
This blog post is about the week-long discussions and activities included a conversation on agricultural scaling between Loraine Ronchi, a Canadian economist, World Bank secondee, and CGIAR senior policy advisor, and Agnes Kalibata, a renowned African agricultural scientist, policymaker, and global leader internationally recognized in the arena of food systems transformation.